T Cell Recruitment in the Brain during Normal Aging - Gemechu, Jickssa Mulissa; Bentivoglio, Marina (Frontiers in Cellular Neuroscience, 2012)
Abstract Aging-related changes in the peripheral immune response are well documented, but less is known about changes of the immune response in the central nervous system. Reactivity of microglia, effectors of the brain innate immunity, is known to increase in the aged brain, but little attention has been hitherto devoted to T cell recruitment. Data in rodents point to a gradual enhancement of T cell homing to the brain in the steady state since the middle age. Experimental findings also point to enhanced transmigration of lymphocytes as part of an amplified response of the aging brain to acute exogenous inflammatory insults. Thus, available data support the capacity of the aged brain to mount a robust immune response, in contrast with peripheral immunity decline, and indicate that such central response involves recruitment of lymphocytes. These findings open many questions, including blood-brain barrier molecular regulation and infiltrated T cell subtypes during normal aging. The crosstalk between T cells, glia and neurons also remains to be clarified in the aged brain parenchyma. This intercellular dialogue and related signaling could be relevant for both protection of the aged brain and its vulnerability to neurological disease.